Ste20-like kinase SLK, at the crossroads: A matter of life and death - Al-Zahrani, Khalid N. (Landes Bioscience, 2013)
Reorganization of the cytoskeleton is necessary for apoptosis, proliferation, migration, development and tissue repair. However, it is well established that mutations or overexpression of key regulators contribute to the phenotype and progression of several pathologies such as cancer. For instance, c-src mutations and the overexpression of FAK have been implicated in the invasive and metastatic process, suggesting that components of the motility system may represent a new class of therapeutic targets. Over the last several years, we and others have established distinct roles for the Ste20-like kinase SLK, encompassing apoptosis, growth, motility and development. Here, we review the SLK field from its initial cloning to the most recent findings from our laboratory. We summarize the various roles of SLK and the biochemical mechanisms that regulate its activity. These various findings reveal very complex functions and pattern of regulation for SLK in development and cancer, making it a potential therapeutic target.